Effect of COVID-19 precautions on the gut microbiota and nosocomial infections. (1st January 2021) - Rashidi, Armin; Ebadi, Maryam; Rehman, Tauseef Ur; Elhusseini, Heba; Nalluri, Harika; Kaiser, Thomas; Holtan, Shernan G; Khoruts, Alexander; Weisdorf, Daniel J.; Staley, Christopher
ABSTRACT: COVID-19 precautions decrease social connectedness. It has been proposed that these measures alter the gut microbiota, with potential clinical consequences. We tested this hypothesis in patients with acute myeloid leukemia (AML) receiving inpatient chemotherapy, a population with extensive exposure to the nosocomial setting and at high risk for infections. Hospitalized patients with AML contributed stool samples to a biorepository protocol that was initiated before COVID-19 and continued without change through the pandemic. Patient-, disease-, and treatment-related characteristics remained the same in the two eras and the only change in clinical care was the implementation of COVID-19 precautions in March 2020. The incidence of all-cause nosocomial infections during the pandemic was lower than in the pre-COVID-19 era. Multivariable analysis revealed an imprint of COVID-19 precautions in the gut microbiota as a viable mechanistic explanation. In conclusion, COVID-19 precautions alter the gut microbiota, thereby mediating pathogen susceptibility and nosocomial infections.